1997
DOI: 10.1046/j.1365-2516.1997.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and potential usefulness of liver biopsy in HIV‐seropositive haemophiliacs employing a transjugular venous approach

Abstract: Chronic liver disease has affected a majority of haemophiliacs exposed to factor VIII and factor IX concentrates before effective viral attenuation techniques were introduced. Progressive hepatitis and liver failure have increasingly become causes of morbidity, especially in haemophilia patients also seropositive for HIV. Encouraging reports of recombinant alpha interferon to reverse the histological, laboratory and clinical deterioration of chronic active hepatitis justifies obtaining liver biopsies to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Only two smaller studies (with sample sizes of 6 and 13) have examined the safety of the transjugular approach in patients with congenital bleeding disorders [21,22]. Gupta et al [22] used more aggressive hemostasis prophylaxis, but Dimichele et al [21] used prophylaxis regimens similar to our own. There were no significant bleeding complications noted in either Gupta's or Dimichele's cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Only two smaller studies (with sample sizes of 6 and 13) have examined the safety of the transjugular approach in patients with congenital bleeding disorders [21,22]. Gupta et al [22] used more aggressive hemostasis prophylaxis, but Dimichele et al [21] used prophylaxis regimens similar to our own. There were no significant bleeding complications noted in either Gupta's or Dimichele's cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Logically, TJLB associated with adequate factor replacement has been proposed for patients with CBD infected with HCV (Makris et al , 2001). However, only a few series of patients with CBD have been reported with this technique to date (Gupta et al , 1997; DiMichele et al , 2003). Gupta et al (1997) reported the results of TJLB in a cohort of six HIV‐positive but HCV‐negative patients with CBD.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few series of patients with CBD have been reported with this technique to date (Gupta et al , 1997; DiMichele et al , 2003). Gupta et al (1997) reported the results of TJLB in a cohort of six HIV‐positive but HCV‐negative patients with CBD. DiMichele et al (2003) reported their experience of 13 TJLB in adult CBD patients with HCV infection without significant morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort experienced no procedure‐associated haemorrhage with the use of a less‐stringent haemostasis prophylaxis and a shorter hospitalization period than that previously described for haemophilia patients by Gupta et al . [15]. However, neither the factor replacement requirement nor period of hospitalization was necessarily shortened in comparison to similar reported cohorts of patients who underwent percutaneous liver biopsy [12–14].…”
Section: Discussionmentioning
confidence: 99%